The Effect of State Property Utilization and Benefits on PNBP Receipts Which Impact Employee Performance in KSOP Utama and KSOP Class I in the Directorate General of Sea Transportation - Mora, Priscilia; Nurbaety, Intan; Barasa, Larsen; Sumali, Bambang; Malau, April Gunawan; Nurhasanah, Meilinasari (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the effect of utilization and benefits of State-Owned Assets (SOA) on the receipts of Non-Tax State Revenue (PNBP) and their impact on employee performance at KSOP Utama and KSOP Class I within the Directorate General of Sea Transportation. The research background is based on several issues such as suboptimal utilization of SOA, bureaucratic obstacles, lack of facilities and training for employees, as well as unstable PNBP receipts that affect employee performance. This study focuses on the period from 2020 to 2024 with a population of 2,418 civil servants and a sample of 343 respondents selected using sampling techniques based on the Taro Yamane formula. The research method used is a quantitative approach with primary data collected through questionnaires measuring respondents' perceptions regarding SOA utilization and benefits, PNBP receipts, and employee performance. Data analysis was conducted using Structural Equation Modeling (SEM) to test the relationships between variables both simultaneously and partially. The results show that the utilization and benefits of SOA have a direct and simultaneous positive and significant effect on PNBP receipts. Furthermore, PNBP receipts also have a positive and significant impact on employee performance. Additionally, the utilization and benefits of SOA influence employee performance both directly and indirectly through the mediation of PNBP receipts. These findings underscore the importance of effective and efficient management and utilization of SOA as a sustainable source of state revenue, while also serving as a supporting factor for improving employee performance. This study provides practical implications for the development of better SOA management policies and the enhancement of human resource capacity at KSOP Utama and KSOP Class I. The research also broadens the empirical understanding of the strategic role of SOA in supporting government institutional performance, particularly in the maritime transportation sector.